Program of promotion of sexual health in students of an educational institution in Huanuco - Bacilio Cruz, Silvia Lina (2019)
Objective. To determine the effectiveness of the sexual and reproductive health promotion program in improving knowledge and changing attitudes in students from 2018 milagro de fatima educational institution. Methods. An applicative, observational, transversal, retro-prospective and analytical study was carried out. the sampling was randomly stratified, with a sample of 201 students in grades 3-5 of secundary school. the instruments used were the sexual and reproductive health knowledge questionnaire and the sexual and reproductive health attitude scale. to test the hypothesis, he student t test was used, with which the effectiveness of the sexual and reproductive health promotion programme was evaluated. Results. There were statistically significant differences in the average of the pre-test scores regarding the post-test ones on the evaluation of sexual and reproductive health knowledge (t= 14,254 and p= 0,000). it was also found that there are statistically significant differences in the average of the scores obtained in the pre test regarding the post one on the evaluation of attitudes towards sexual and reproductive health (t= 6,045 and p= 0,000). Conclusion. The sexual and reproductive health promotion programme was effective in improving knowledge and changing attitudes among students at the milagro de fatima educational institution.